Network Neutrality: Potential impact on free speech and the right to information - Wyszyński, Jacek (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2017)
The ongoing debate in the EU and the US over the shape of the Internet focuses mainly on the technological and economical aspects of the issue. This paper is meant to be an introduction to the debate on the impact of the network neutrality on free speech and the right to information in the field of political science. The author tries to identify potential threats from the economic, technological and political perspective, as they are strongly interconnected. Fundamental human rights can benefit from enforcing network neutrality regulations; however, a much more important issue is related to the question of what would happen to the freedom of speech and the right of information if the regulations were gone.

Debata nad kształtem Internetu, która toczy się w Stanach Zjednoczonych i w Europie, skupia się głównie na aspektach technologicznych i ekonomicznych. Celem niniejszego artykułu jest wprowadzenie do dyskusji na temat wpływu neutralności sieciowej na wolność słowa i prawo do informacji na gruncie nauk politycznych. Autor próbuje zidentyfikować potencjalne zagrożenia na z perspektywy ekonomicznej, technologicznej, a także politycznej. Wdrożenie przepisów narzucających neutralność sieciową będzie niewątpliwie korzystne dla podstawowych praw człowieka. Jednak nawet ważniejszą kwestią jest pytanie o stan Internetu, w przypadku gdyby tych przepisów zabrakło.
Neutralność sieciowa i jej potencjalny wpływ na wolność słowa i prawo do informacji
Keywords: network neutrality; freedom of speech; right to information; neutralność sieciowa; wolność słowa; prawo do informacji